The lost gold - Harrison, Paula; Tancredi, Sharon (London nosy crow c 2018, 2018)
Princess Isabella loves her rainforest kingdom and its amazing creatures. So she's very worried when treasure hunters start digging up the forest and scaring all the animals. A baby monkey becomes trapped and Isabella will need all her bravery to save it. Thank goodness she has the other Rescue Princesses to help her
English stories
Keywords: English fictions